Dielectric characterization of geochemical properties of liquid hydrocarbons from 25 °C to 125 °C. (15th March 2021) - Alvarez, Jose Oliverio; Jacobi, David; Althaus, Stacey; Elias, Solomon
Abstract: Complex permittivity measurements were conducted for four crude oils and a gas condensate at temperatures ranging from 25 °C to 125 °C. The measurements were conducted using a liquid test fixture and results are reported for frequencies between 50 kHz and 5 MHz. Geochemical analyses were performed, and the main components of the liquid hydrocarbons were identified and, in the process, both the provenance and genesis of the crude oils were determined. Analysis of the permittivity measurements show that, within uncertainty, the real part of the dielectric permittivity spectra can be related back to the density (API), maturity, and secondary chemical alteration. The behavior of the imaginary part, although dominated by the conductivity, which is correlated to the asphaltene, metal, and aromatic content of the hydrocarbons studied, showed an interesting result that lead to the prediction of inseparable water, which was further verified by Nuclear Magnetic Resonance (NMR) measurements. In addition, results at 25 °C were combined with those obtained from two high accuracy, multipoint re-entrant resonant cavities for nine different frequencies between 170 MHz and 8.6 GHz. Results predict relaxation process between 5 MHz and 100 MHz, in agreement with the literature.